The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1128/aem.02643-08
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pythium oligandrum Biocontrol on Fungal and Oomycete Population Dynamics in the Rhizosphere

Abstract: Fungal and oomycete populations and their dynamics were investigated following the introduction of the biocontrol agent Pythium oligandrum into the rhizosphere of tomato plants grown in soilless culture. Three strains of P. oligandrum were selected on the basis of their ability to form oospores (resting structures) and to produce tryptamine (an auxin-like compound) and oligandrin (a glycoprotein elicitor). Real-time PCR and plate counting demonstrated the persistence of large amounts of the antagonistic oomyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 58 publications
0
19
1
Order By: Relevance
“…The management of plant diseases with C. rosea involves several mechanisms such as mycoparasitism, antagonist action, induced resistance, and competition, which enhance the performance of the biocontrol fungus (Mouekouba et al 2014; Zhang et al 2008). In addition, colonization of the biocontrol isolates on plants during the growing season can also greatly affect the control efficiency (Vallance et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The management of plant diseases with C. rosea involves several mechanisms such as mycoparasitism, antagonist action, induced resistance, and competition, which enhance the performance of the biocontrol fungus (Mouekouba et al 2014; Zhang et al 2008). In addition, colonization of the biocontrol isolates on plants during the growing season can also greatly affect the control efficiency (Vallance et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…), allowing some nonpathogenic species to induce positive PSFs by suppressing primary pathogenic species (Vallance et al. ), whereas other co‐occurring species may have no apparent impact on primary pathogens (Suffert and Guibert ). A more detailed understanding of the distribution and dynamics of pathogens, nonpathogens, and host‐associated mutualists and commensals will provide greater insights for understanding plant–microbe interactions, and the roles they play in plant community dynamics and plant invasions.…”
Section: Discussionmentioning
confidence: 99%
“…Authors presumed the existence of a balanced antagonism between the virulence of the colonizing endophyte and the plant defence response. Vallance et al (2009) studied the influence of a biocontrol agent (Pythium oligandrum) on fungal and oomycete population dynamics in the rhizosphere and, surprisingly, found that, with few exceptions, there were no significant differences between the microbial ecosystems inoculated with P. oligandrum and those that were not treated. In another study, qPCR proved to be more sensitive than dilutions on a selective media to detect and quantify a potential BCA (Plectosphaerella cucumerina) of potato cyst nematodes in soil (Atkins et al 2003).…”
Section: Quantification Of Field-applied Biocontrol Agentsmentioning
confidence: 99%